Controversial Leaders and Strategic Policies Case Study: The Government of DKI Jakarta during the Leadership Period of Basuki Tjahaya Purnama - Muhammad Faisal; Farhan, Muhamad (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2021)
Leadership is a person's ability to provide good role models and performance. Leadership is also a person's ability to move staffs to achieve organizational goals. A leader is required to create innovations that can give birth to strategic policies in running the wheels of the organization. Ahok is known to many as a controversial leader. Ahok's arrogant attitude in the eyes of some people was considered negative. Ahok's attitude was also considered bad in the eyes of the Moslems regarding his statement of the Al-Maidah verse 51. However, Ahok was also known as an innovative leader. The media had highlighted Ahok's actions in leading Jakarta. One of Ahok's strategic policies was the Jakarta Smart Card which is expected to provide access to education at a minimum of up to high school / vocational school for Jakarta residents who are less able. The green open space program was also Ahok's strategic policy that functions ecologically and as a place for social activities in public spaces. Both programs were considered positive and even continued and developed by the next Governor, Anies Baswedan. This research method uses descriptive qualitative analysis. The author seeks literature from literature studies and seeks Ahok's strategic programs from online and printed news media. In conclusion, Ahok is a controversial leader, but he is also an innovative leader.